Morphological and Molecular Characterization of Pestalotiopsis sp. Associated with Leaf Spot Disease in Eucalyptus pellita - Endrawati, Silvia; Haryani, Tri Saptari; Lelana, Neo Endra (Universitas Pakuan, 2025)
Leaf spot disease is one of the most common foliar infections affecting Eucalyptus pellita, a fast-growing tree species widely cultivated for pulp and paper industries in Indonesia. This study aimed to isolate and identify the fungal pathogen associated with the disease through morphological and molecular characterization. Symptomatic leaves were collected from E. pellita stands in KHDTK Parungpanjang, and fungal isolation was performed on Potato Dextrose Agar (PDA). Morphological observations revealed that the isolated fungus exhibited white colonies with purple pigmentation at the center and conidia containing four septa—typical characteristics of Pestalotiopsis species. Molecular identification was conducted using Internal Transcribed Spacer (ITS) region sequencing of rDNA, followed by BLAST analysis against the NCBI GenBank database. Sequence alignment and phylogenetic tree reconstruction confirmed that the isolate (PT.E002) shared 100% similarity with Pestalotiopsis mangiferae, P. clavispora, P. maculans, and P. microspora. The phylogenetic analysis indicated a close relationship between the PT.E002 isolate and P. maculans. These results validate the presence of Pestalotiopsis sp. as the main pathogen associated with leaf spot disease in Eucalyptus pellita. The integration of morphological and molecular analyses enhances the accuracy of pathogen identification, contributing valuable insights for forest disease management and sustainable Eucalyptus cultivation programs.